Multi-purpose cash transfers and health among vulnerable Syrian refugees in Lebanon: a prospective cohort study - Emily Lyles; Jakob Arhem; Ghada El Khoury; Antonio Trujillo; Paul Spiegel; Ann Burton; Shannon Doocy (BMC, 2021)
Abstract Background Multipurpose cash transfers (MPCs) are used on a widespread basis in the Syrian refugee response; however, there is little to no evidence as to how they affect health in humanitarian crises. Methods A prospective cohort study was conducted from May 2018 through July 2019 to evaluate the impact of MPCs on health care-seeking and expenditures for child, adult acute, and adult chronic illness by Syrian refugees in Lebanon. Households receiving MPCs from UNHCR were compared to control households not receiving UNHCR MPCs. Results Care-seeking for childhood illness was consistently high in both MPC and non-MPC households. An increased proportion of households did not receive all recommended care due to cost; this increase was 19.3% greater among MPC recipients than controls (P = 0.002). Increases in child hospitalizations were significantly smaller among MPC recipients than controls (DiD -6.1%; P = 0.037). For adult acute illnesses, care-seeking increased among MPC recipients but decreased in controls (adjusted DiD 11.3%; P = 0.057); differences in change for other utilization outcomes were not significant. The adjusted difference in change in the proportion of MPC households not receiving recommended chronic illness care due to cost compared to controls was − 28.2% (P = 0.073). Access to medication for adult chronic illness also marginally significantly improved for MPC households relative to controls. The proportion of MPC recipients reporting expenses for the most recent child and adult acute illness increased significantly, as did the [log] total visit cost. Both MPC and control households reported significant increases in borrowing to pay for health expenses over the year study period, but differences in change in borrowing or asset sales were not significant, indicating that MPC was not protective against for household financial risks associated with health. Conclusions While MPC may have shown some positive effects, findings were mixed and MPC appears insufficient on its own to address health utilization and expenditures. A broader strategy addressing Syrian refugee health in Lebanon is needed of which MPC should be incorporated, with additional support such as additional conditional cash transfers for health.